Understanding the public-private sector wage gap in Germany: New evidence from a Fixed Effects quantile Approach∗ - Bonaccolto-Töpfer, Marina; Castagnetti, Carolina; Prümer, Stephanie (Economic Modelling, 2022)
The public-private sector wage gap is an important labor market indicator, reflecting sectoral differences in wage and recruitment policies. We provide new evidence on this sectoral gap throughout the wage distribution in Germany. Using data from the German Socio-Economic Panel (1984–2017), we decompose the wage gap and control for unobservable factors that endogenously determine the occupational sector choice. Our estimates confirm the result in the literature that women benefit from working in the public sector. For men, we find that they are unambiguously disadvantaged, with higher remuneration in the private sector across the entire wage distribution. This result contrasts with previous findings in the literature. Moreover, our findings show that taking endogenous selection into account substantially changes the decomposition of the gap, and it is crucial for assessing alternative policy measures.
CRIS-Team Scopus Importer:2022-09-30
Keywords: Germany; Public-private sector wage gap; Quantile regression for panel data; Gender